Differential protein expression during growth on model and commercial mixtures of naphthenic acids in Pseudomonas fluorescens Pf-5 - McKew, Boyd A.; Johnson, Richard; Clothier, Lindsay; Skeels, Karl; Ross, Matthew S.; Metodiev, Metodi; Frenzel, Max; Gieg, Lisa M.; Martin, Jonathan W.; Hough, Michael A.; Whitby, Corinne (My University, 2021)
Naphthenic acids (NAs) are carboxylic acids with the formula (CnH2n+ZO2) and are among the most toxic, persistent constituents of oil sands process-affected waters (OSPW), produced during oil sands extraction. Currently, the proteins and mechanisms involved in NA biodegradation are unknown. Using LC-MS/ MS shotgun proteomics, we identified proteins overexpressed during the growth of Pseudomonas fluorescens Pf-5 on a model NA (4′-n-butylphenyl)- 4-butanoic acid (n-BPBA) and commercial NA mixture (Acros). By day 11, >95% of n-BPBA was degraded. With Acros, a 17% reduction in intensity occurred with 10–18 carbon compounds of the Z family −2 to −14 (major NA species in this mixture). A total of 554 proteins (n-BPBA) and 631 proteins (Acros) were overexpressed during growth on NAs, including several transporters (e.g., ABC transporters), suggesting a cellular protective response from NA toxicity. Several proteins associated with fatty acid, lipid, and amino acid metabolism were also overexpressed, including acyl-CoA dehydrogenase and acyl-CoA thioesterase II, which catalyze part of the fatty acid beta-oxidation pathway. Indeed, multiple enzymes involved in the fatty acid oxidation pathway were upregulated. Given the presumed structural similarity between alkyl-carboxylic acid side chains and fatty acids, we postulate that P. fluorescens Pf-5 was using existing fatty acid catabolic pathways (among others) during NA degradation.
Keywords: naphthenic acids; oil sands process-affected water; proteomics; Pseudomonas fluorescens; tailing ponds; toxicity